Antioxidant Activity of Bay (Syzygium polyanthum [Wight] Walp) Leaf Extract Toner - Jamilatun, Makhabbah; Lukito, Pradea Indah; Zahra, Melda Aulia (Journal of Health Science and Medical Therapy, 2025)
Facial skin susceptible to oxidative stress due to free radicals can be prevented by increasing the amount of antioxidants. Bay leaf extract is known to have antioxidant activity, it can be formulated into a toner. The purpose of this study was to determine the physical quality and antioxidant activity of bay leaf extract toner. The method used was experimental, with four formulas of variations in the concentration of bay leaf extract addition, namely F0 (0%), F1 (1.5%), F2 (3%), and F3 (6%). The extract was obtained through maceration using 96% ethanol, and then tested for physical quality consisting of organoleptic, pH and viscosity, and antioxidant activity with the DPPH method. The results showed an extract yield of 12.58%. The best formula for bay leaf extract toner preparation was F2, with physical quality including liquid organoleptic, light brown color, the distinctive odor of bay leaf extract; pH 4.74; viscosity 3.81 cP; and IC50 of 46,090 ppm with a very strong antioxidant activity category. Conclusion, bay leaf extract has the potential to be a natural active ingredient in skin care products that is effective in protecting the skin from the effects of free radicals.